2009
DOI: 10.1007/s12308-009-0031-2
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of B cell lymphoma to histiocytic sarcoma: somatic mutations of PAX-5 gene with loss of expression cannot explain transdifferentiation

Abstract: Transdifferentiation of B cell lymphoma of germinal center cell origin to histiocytic sarcoma has recently been described but is a rare occurrence. The cause for loss of B cell differentiation in these lymphomas is unknown. We investigated whether somatic hypermutation of the PAX-5 gene, a transcription factor that is important for maintaining B cell identity and is frequently mutated in B cell lymphomas of germinal center cell origin, might be a cause for loss of PAX-5 expression and thus B cell phenotype. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Some cases of HS occur subsequent to or concurrent with B-or T-lymphoblastic lymphoma/leukemia or mature B-cell neoplasms such as follicular lymphoma, chronic lymphocytic leukemia, mantle cell lymphoma, extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue, splenic marginal zone lymphoma and diffuse large B-cell lymphoma. 11,12,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Most associated mature B-cell lymphomas are low-grade B-cell lymphomas. The interval between the occurrence of lymphoma and that of HS is between 2 months and 17 years.…”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cases of HS occur subsequent to or concurrent with B-or T-lymphoblastic lymphoma/leukemia or mature B-cell neoplasms such as follicular lymphoma, chronic lymphocytic leukemia, mantle cell lymphoma, extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue, splenic marginal zone lymphoma and diffuse large B-cell lymphoma. 11,12,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Most associated mature B-cell lymphomas are low-grade B-cell lymphomas. The interval between the occurrence of lymphoma and that of HS is between 2 months and 17 years.…”
Section: Definitionmentioning
confidence: 99%
“…30,33,35 In addition, some cases showed nuclear positivity of OCT-2, a B-cellassociated transcription factor. Of interest, Chen et al recently reported that 4 of 7 sporadic HS cases with detectable clonal IG gene rearrangement expressed OCT-2.…”
Section: Immunophenotypementioning
confidence: 99%
“…17,18 The types of primary B-cell malignancy include FL [8][9][10][11][12][13] in 12 cases, CLL/ SLL 14,15 in 8 cases, DLBCL 9 in 1 case, and splenic marginal zone lymphoma 12 in the remaining 1 case. Secondary neoplasms include histiocytic sarcoma (HS) [8][9][10][11][12][13]15 in 15 cases, interdigitating dendritic cell sarcoma (IDCS) 8,14,15 in 6 cases, and Langerhans cell sarcoma 15 in the remaining 1 case. Of note, 3 cases demonstrated a biphasic presentation of neoplasms secondary to FL, or a divergent clonal evolution, with concurrent HS and DLBCL in 2 cases (cases 9 and 11 in the Table) and sequential development of HS and DLBCL in 1 case (case 13).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Because of the infrequency, H/DS, either subsequent to or concurrent with B-cell lymphoma, is often initially suspected to be large cell transformation (DLBCL), which is commonly seen in indolent B-cell lymphomas, such as FL and CLL/SLL. Of 22 cases reported in the literature, [8][9][10][11][12][13][14][15] all the cases with large cells noted on the sections, either subsequent to or concurrent with B-cell malignancies, were thought to be DLBCL related to the primary B-cell neoplasms at initial evaluation. Only after extensive immunohistochemical analysis was a histiocytic/dendritic cell phenotype identified and diagnosis of H/DS established.…”
Section: Histologic and Immunophenotypic Findingsmentioning
confidence: 99%
See 1 more Smart Citation